2009
DOI: 10.2165/00023210-200923030-00005
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacotherapy in Paediatric Obsessive-Compulsive Disorder

Abstract: Our study suggests that putative variables associated with response to pharmacological treatment of paediatric OCD can be defined, and can help improve treatment strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
1
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 27 publications
2
39
1
2
Order By: Relevance
“…7 This finding has been reported consistently across many studies of BD-OCD. 7,15,16,23,24 Our study found a higher number of suicidal attempts in BD-OCD. Many previous studies also report the same finding.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…7 This finding has been reported consistently across many studies of BD-OCD. 7,15,16,23,24 Our study found a higher number of suicidal attempts in BD-OCD. Many previous studies also report the same finding.…”
Section: Discussionsupporting
confidence: 51%
“…4,7,8,12 OCD in BD is a poor prognostic factor too, as poor treatment response and polypharmacy are well documented in BD-OCD comorbidity. 7,[13][14][15] A recent large sample study from India showed that OCD is severe in BD-OCD. 9 In another study, severity of OCD in BD was significantly higher when compared with pure OCD and subjects had moderate to severe scores on the Y-BOCS severity scale.…”
Section: Introductionmentioning
confidence: 99%
“…When restricting the analysis to studies with sample size greater than 250, the BD-OCD prevalence range was narrower (11-15.7%) (17,51,53), and the mean prevalence rate of BD-I comorbidity was 3.7%, while BD-II was 9.5% (17,51,53,58). Hospital-based studies conducted in OCD children and adolescents described prevalence of comorbid BD ranging between 1.8% and 35.8% (43,(59)(60)(61)(62)(63). Only one study differentiated BD comorbidity by type in child and adolescent population (62).…”
Section: Included Studiesmentioning
confidence: 99%
“…Most studies herald the usefulness of antipsychotics as an augmenting agent to SSRIs (Masi et al, 2009). One study showed that over half of children who received an atypical antipsychotic as an augmenting strategy for OCD showed improvement (Masi et al, 2009).…”
Section: Risperidonementioning
confidence: 99%
“…Most studies herald the usefulness of antipsychotics as an augmenting agent to SSRIs (Masi et al, 2009). One study showed that over half of children who received an atypical antipsychotic as an augmenting strategy for OCD showed improvement (Masi et al, 2009). In adults with treatment-refractory OCD, antipsychotics have the largest body of evidence supporting their use as augmenting agents (Decloedt & Stein, 2010).…”
Section: Risperidonementioning
confidence: 99%